COMPARISON OF INTERNATIONAL SYSTEMS IN FAMILY DISPUTE RESOLUTION - Ridwan; Erman Gani; Muhammad Alpi Syahrin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Family dispute resolution is an essential component of the legal system that reflects the social, cultural, and legal values of a country. This study aims to analyze the comparison of family dispute resolution systems across different countries using a comparative law approach. The method employed is normative legal research with a comparative analysis of several legal systems, namely civil law, common law, and Islamic law. The results indicate that there are significant differences in the mechanisms for resolving family disputes, both through litigation and alternative dispute resolution methods such as mediation. Countries adopting the common law system tend to emphasize flexibility and mediation, whereas civil law systems rely more on structured formal judicial processes. Meanwhile, the Islamic legal system highlights deliberation and reconciliation as primary approaches. This research is expected to provide a global perspective for the development of family dispute resolution systems in Indonesia